Sistem Informasi Pengelolaan Rekam Medis Rumah Sakit Menggunakan Java - Muzzammil Haitami; Intan Mutia; Ni Wayan Parwati Septiani (Universitas Indraprasta PGRI Jakarta, 2020)
In this era, the development of information technology plays an important role in various sectors of human life. Especially the business in the field of medical records of patients in hospitals. The impact of the development of information technology is very broad, this can be felt in various aspects of life, one of these aspects can be felt in various aspects that are affected by technological advances in the health sector. Field which is one of the supporting factors of human life, and can be said that health is the most important factor in human life. The design of this information system aims to create information systems for processing medical records of patients in providing accurate data for administration and pharmacies. Management of medical records in hospitals is designed using an integrated and computerized information system with hospital databases. in building this system used system design tools that are Data Flow Diagrams (DAD), context, Zero and Detailed and by using the Java programming language with NetBeans and MySQL databases using XAMPP.